Effect of prolonged exercise on the passage of a solid meal through the stomach and small intestine. Issue 11 (November 1982) - Cammack, J; Read, N W; Cann, P A; Greenwood, B; Holgate, A M
Abstract : The effect of intermittent moderate exercise on the passage of a solid meal, labelled with radioactive Technetium sulphur colloid, through the stomach and small intestine was investigated by paired studies on seven healthy volunteers. Measurements of gastric radioactivity and breath hydrogen exertion were recorded every 10 minutes while subjects exercised in a controlled manner while seated on a bicycle ergometer. These were compared with values obtained during a separate experiment while the same subjects sat upright in a chair. Exercise significantly accelerated gastric emptying (control t 1/2 = 1.5 +/- 0.1 h; exercise t 1/2 = 1.2 +/- 0.1 h; p less than 0.02) but had no significant effect on small bowel transit time.